Etnomatematika: Meningkatkan Minat dan Pemahaman Matematika melalui Media Permainan Congklak - Kayla Nurazizah (Prodi Pendidikan Matematika, Fakultas Tarbiyah dan Ilmu Keguruan IAIN Langsa, 2023)
This research aims to find out the many cultural diversities found in Indonesia that can be used as learning media, one of which is the traditional game of congklak. The relationship between culture and mathematics in the game of congklak can be used as a new innovation in learning. The method used in this research is qualitative with an ethnographic approach which is an approach to obtain information about the congklak game in Kampung Parung Belimbing, Depok City based on the records obtained from data collection. The new innovation of the traditional game of congklak can be used as a new paradigm or thought about learning mathematics involving a culture. The congklak game has several learning concepts, namely the concept of building space and number operations. With the results of this study proving that mathematics learning can be applied to everyday life and changing children's perspectives on mathematics that mathematics learning can be learned and understood easily and fun with concrete learning and also students can be able to continue to preserve traditional games in the home and home environment.